SPROGMØDET SET MED KULTURTEORETISKE BRILLER - Risager, Karen (Tidsskriftet Antropologi, 2007)
The aim of this article is to show how language studies and cultural studies can develop the interface between the two fields of study through a focus on language as culture. Here the emphasis is not on the form aspect of language – its grammar and phonology – but on the content side, its meaning-carrying and meaningcreating aspect. The article looks at language and language encounters through culture – theoretical glasses. It analyses linguistic practice as socially structured meaning at both micro and macro levels. The concept of languaculture is useful for this purpose. The concept may be analysed in three dimensions: a semanticpragmatic, a poetic, and an identity dimension. These dimensions are illustrated in an analysis of the slogan Buy some petit souvenir aus Dänemark! seen as a part of the multilingual space of tourism in Europe.